Inkubasi Pemasaran dan Digitalisasi Bisnis pada Badan Usaha Milik Desa Pemenang Desa Brilian di Provinsi Riau - Berri Brilliant Albar; Ares Albirru Amsal (Warta Pengabdian Andalas, 2024)
The Deepening Desa Brilian Program is an initiative aimed at enhancing rural economies through mentoring in marketing and business digitalization for Village-Owned Enterprises (BUMDes). The objective of this program is to maximize the economic potential of villages by increasing financial literacy and applying digital technologies in local business management. The program involved 72 villages in Riau and West Sumatra provinces, with direct mentoring focused on the three best-performing villages: Bukit Gajah, Pasir Baru, and Sialang Kubang. The methodology utilized in this program included an e-learning and community development approach, where participants received mentoring on modern marketing strategies and digital business management. The mentoring was conducted through 8 weeks of online sessions and 5 direct mentoring sessions in the field. The results indicate that implementing consumer-oriented marketing strategies and optimizing the use of digital technologies significantly improved the efficiency of BUMDes business operations. These villages were able to develop more strategic and innovative marketing plans, while also managing their businesses more effectively through digital platforms. Overall, the program successfully enhanced financial literacy, operational efficiency, and economic potential in the participating villages. In conclusion, the Deepening Desa Brilian Program has had a significant impact on strengthening the economic capacity of villages through modern marketing approaches and business digitalization. The outcomes of this mentoring program can serve as a model for other villages across Indonesia to maximize their local economic potential.